2011
DOI: 10.1055/s-0031-1296299
|View full text |Cite
|
Sign up to set email alerts
|

The new generation of intravenous iron: chemistry, pharmacology, and toxicology of ferric carboxymaltose

Abstract: An ideal preparation for intravenous iron replacement therapy should balance effectiveness and safety. Compounds that release iron rapidly tend to cause toxicity, while large molecules can induce antibody formation and cause anaphylactic reactions. There is therefore a need for an intravenous iron preparation that delivers appropriate amounts of iron in a readily available form but with minimal side effects and thus with an excellent safety profile. In this paper, a review is given on the chemistry, pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 5 publications
4
65
0
1
Order By: Relevance
“…Animal studies have shown it to be rapidly eliminated from the plasma, giving minimal risk of large amounts of ionic iron in the plasma. In iron deficient rats, most of the iron has been incorporated into new erythrocytes by 28 d (Funk et al, 2010).…”
Section: Fast Acting Intravenous Iron Preparationsmentioning
confidence: 99%
“…Animal studies have shown it to be rapidly eliminated from the plasma, giving minimal risk of large amounts of ionic iron in the plasma. In iron deficient rats, most of the iron has been incorporated into new erythrocytes by 28 d (Funk et al, 2010).…”
Section: Fast Acting Intravenous Iron Preparationsmentioning
confidence: 99%
“…2, the pharmacokinetic of IV iron is substantially different from that of oral iron. Once injected in the bloodstream (hence circumventing problems in intestinal absorption), IV iron is mainly taken up by macrophages, which subsequently release the element through ferroportin [101]. However, less stable complexes can release variable amount of ferric iron directly in the circulation before macrophage uptake.…”
Section: The Chemistry Of Different IV Iron Preparations and Its Relamentioning
confidence: 99%
“…Together, the toxicity studies undertaken in rats and dogs show that iron accumulation resulting from administration of sucroferric oxyhydroxide is low and below toxic levels, even with long-term use at high doses [42]. Moreover, at clinically-relevant doses of 
40 mg Fe/kg/day, sucroferric oxyhydroxide was not associated with significant increases in liver, spleen or kidney iron values compared with controls after 2 years of administration in rats or after 39 weeks of administration in dogs.…”
Section: Preclinical Data Reviewmentioning
confidence: 99%
“…In humans, iron is stored in ferritin, which consists of an iron (III)-oxyhydroxide core stabilised by a protein shell, and it is transported in transferrin, a glycoprotein consisting of a single polypeptide chain with two iron-binding sites [41, 42]. Iron is mainly stored in the liver and spleen in hepatocytes and macrophages, but the maintenance of iron levels is regulated by absorption in the small intestine [38, 43].…”
Section: Introductionmentioning
confidence: 99%